2020
DOI: 10.1002/pd.5838
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic signatures of recurrent pregnancy losses

Abstract: Objectives To investigate the incidence of chromosomal abnormalities in the products of conception (POC) of patients with spontaneous miscarriages (SM) and with recurrent pregnancy losses (RPL) and to determine biological mechanisms contributing to RPL. Methods During a 20‐year period, 12 096 POC samples underwent classical chromosome analysis. Cytogenetic findings were compared between the SM and RPL cohorts. Results Analysis of RPL cohort has identified an increased incidence of inherited and de novo structu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…This study found a close correlation between miscarriage history and IH, which has been neglected in many studies. Although F GDM, gestational diabetes mellitus; LBW, low birth weight; PPROM, preterm premature rupture of membranes; PROM, premature rupture of membrane -Fisher's exact examination was used for analysis Factors reported in gray were excluded by univariable analysis miscarriage occurs because of many causes, such as parental chromosomal rearrangements and uterine defects, damage to the uterus and endometrium caused by miscarriage should not be ignored [22][23][24]. During placental development, some aspects of angiogenesis precede the generation of the vasculature and lead to remodeling of the vascular plexus into a branched vascular tree to ensure increased nutritional and gas exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found a close correlation between miscarriage history and IH, which has been neglected in many studies. Although F GDM, gestational diabetes mellitus; LBW, low birth weight; PPROM, preterm premature rupture of membranes; PROM, premature rupture of membrane -Fisher's exact examination was used for analysis Factors reported in gray were excluded by univariable analysis miscarriage occurs because of many causes, such as parental chromosomal rearrangements and uterine defects, damage to the uterus and endometrium caused by miscarriage should not be ignored [22][23][24]. During placental development, some aspects of angiogenesis precede the generation of the vasculature and lead to remodeling of the vascular plexus into a branched vascular tree to ensure increased nutritional and gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…This study found a close correlation between miscarriage history and IH, which has been neglected in many studies. Although miscarriage occurs because of many causes, such as parental chromosomal rearrangements and uterine defects, damage to the uterus and endometrium caused by miscarriage should not be ignored [ 22 – 24 ]. During placental development, some aspects of angiogenesis precede the generation of the vasculature and lead to remodeling of the vascular plexus into a branched vascular tree to ensure increased nutritional and gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…However, data from a cytogenetic survey on 10,730 recurrent pregnancy losses (not included in the above-mentioned list of 61 reports), where non-mosaic T14 was detected in about 6% of full aneuploidies, supported the conclusion regarding the low frequency of mosaic T14. The study did not report any case of mosaicism for T14, although mosaic trisomies of chromosomes 16, 13, 2, and 22 were identified in 0.35%, 0.35%, 0.28%, and 0.21% of aneuploid POC [9]. This observation was intriguing since mosaics are more viable than full trisomy carriers.…”
Section: Population Frequencymentioning
confidence: 87%
“…The difference is mainly driven by identification of chromosomal anomalies that cfDNA is unable or fails to detect (such as polyploidy or small copy number variants <7Mb). Polyploidy cases, occurring in 4∼7% of RPL cases, 24 can be diagnosed with cytogenetic culture and single‐nuleotide polymorphism (SNP) array. It can also be identified with SNP‐based cfDNA testing.…”
Section: Discussionmentioning
confidence: 99%